Unleashing Natural Killer Cells in the Tumor Microenvironment–The Next Generation of Immunotherapy? - Ben-Shmuel, Aviad; Biber, Guy; Barda-Saad, Mira (Frontiers in Immunology, 2020)
The emergence of immunotherapy for cancer treatment bears considerable clinical promise. Nevertheless, many patients remain unresponsive, acquire resistance, or suffer dose-limiting toxicities. Immune-editing of tumors assists their escape from the immune system, and the tumor microenvironment (TME) induces immune suppression through multiple mechanisms. Immunotherapy aims to bolster the activity of immune cells against cancer by targeting these suppressive immunomodulatory processes. Natural Killer (NK) cells are a heterogeneous subset of immune cells, which express a diverse array of activating and inhibitory germline-encoded receptors, and are thus capable of directly targeting and killing cancer cells without the need for MHC specificity. Furthermore, they play a critical role in triggering the adaptive immune response. Enhancing the function of NK cells in the context of cancer is therefore a promising avenue for immunotherapy. Different NK-based therapies have been evaluated in clinical trials, and some have demonstrated clinical benefits, especially in the context of hematological malignancies. Solid tumors remain much more difficult to treat, and the time point and means of intervention of current NK-based treatments still require optimization to achieve long term effects. Here, we review recently described mechanisms of cancer evasion from NK cell immune surveillance, and the therapeutic approaches that aim to potentiate NK function. Specific focus is placed on the use of specialized monoclonal antibodies against moieties on the cancer cell, or on both the tumor and the NK cell. In addition, we highlight newly identified mechanisms that inhibit NK cell activity in the TME, and describe how biochemical modifications of the TME can synergize with current treatments and increase susceptibility to NK cell activity.